FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA PERAWAT DALAM KEPERAWATAN KESEHATAN MASYARAKAT (PERKESMAS) DI PUSKESMAS - Anggun " Emelia; Febriana " Sabrian; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The nurse is the main implementer of activities in the health center who able to lead self-public system for protecting and improving community health degree, so the implementation of public health nursing in community health center will be influenced by nurse’s performance. The purpose of the study was to identify the factors which were related to the nurse performance in public health nursing at community health center. The design of this study was descriptive correlation with cross sectional approach. The number of samples of this study was 77 nurses that were taken usingsimple random sampling technique. This research used questionnaire that has been tested validity and reliability. The analysis used univariate analysis and bivariate with Chi-square test. The result showed for most respondents were in early adulthood (93,5%), diploma level nursing education (68,8%), length of work > 10 years (42,9%), lack of knowledge (45,5%), negative attitude (58,4%), lack of skills (75,3%), heavy workload (64,9%), lack of supervision (63,6%), and performance of the nurses is not optimal (61%). The result of the bivariate analysisshowed that there was a relationship between knowledge (p value = 0,038), skills (p value = 0,026), supervision (p value = 0,007) with  the nurse performance of public health nursing in community health center,  while attitude(p value = 0,351) and workload (p value = 0,618) had no correlation with  the nurse performance. Based on this result, it is recommended to health worker especially nurses to further improve their performanceswhen implementing public health nursing. Keywords: Nurse, Performance, Public Health Nursing